Rupture and reclamation in the life story: the role of early relationships in self-narratives following a forced career transition - Maitlis, S (Elsevier, 2022)
Narrative approaches to the self suggest that forced career transitions disrupt individuals’ self-narratives and motivate their efforts to re-establish narrative coherence. To craft and rework their self-narratives, people draw on a range of relational resources, including relationships with family, friends, and other important people in their lives. In this paper, I explore the link, within individuals’ self-narratives, between people’s working lives following a forced career transition and their early parental relationships. I investigate this through a longitudinal narrative study of 21 professional dancers forced to change career after an injury, drawing on three waves of interviews over an eight-year period. I identify three types of self-narrative – Immersed-Striving, Oppositional-Seeking, and Supportive-Settling – that link a kind of early parental relationship to a kind of post-injury relationship to work. In each of these narratives, dance acts as a transitional object with a specific relational meaning – connection, agency, or direction – that was enacted in participants’ early relationships, and that they sought to re-establish through their post-injury working lives.